2021
DOI: 10.1029/2021jg006374
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Nutrient Addition Affects Water Column Nutrient Processing Rates in River‐to‐Lake Transitional Zones

Abstract: In the Laurentian Great Lakes, nonpoint sources contribute most of the total nutrient load delivered to eutrophic embayments (Maccoux et al., 2016;Robertson & Saad, 2011). However, the export of nutrients from many nonpoint sources (e.g., agriculture) is temporally variable and often associated with water runoff from precipitation events (Withers & Jarvie, 2008). Although nonpoint sources of nutrients contribute to the overall enrichment of surface wa-Abstract Storm-driven nutrient loading from tributaries can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 82 publications
0
13
1
Order By: Relevance
“…(2007) found that there is a slow but steady increase in the phytoplankton standing stock over time in Kaneohe Bay after storm pulse input. Similar processes occur at locations where major rivers flow into lakes (Pearce et al., 2021), but such locations are not dominated by SPM and thus result in nutrient uptake by phytoplankton, including preferential P uptake and increased eutrophication in these lake estuaries.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…(2007) found that there is a slow but steady increase in the phytoplankton standing stock over time in Kaneohe Bay after storm pulse input. Similar processes occur at locations where major rivers flow into lakes (Pearce et al., 2021), but such locations are not dominated by SPM and thus result in nutrient uptake by phytoplankton, including preferential P uptake and increased eutrophication in these lake estuaries.…”
Section: Discussionmentioning
confidence: 86%
“…Such changes are typical of such systems, for example, De Carlo et al (2007) found that there is a slow but steady increase in the phytoplankton standing stock over time in Kaneohe Bay after storm pulse input. Similar processes occur at locations where major rivers flow into lakes (Pearce et al, 2021), but such locations are not dominated by SPM and thus result in nutrient uptake by phytoplankton, including preferential P uptake and increased eutrophication in these lake estuaries. Lin et al (2022) determined the concentration and flux of N species in the river-estuary continuum for the same storm as has been studied in detail here for P species.…”
Section: Effects Of Storms On the Outer Estuary And Implications For ...mentioning
confidence: 88%
“…Furthermore, transformation of gases in the water column or headspace of the microcosm could modify the relative concentrations of GHGs actually emitted from sediments before sampling, for example, oxidation of CH 4 to CO 2 . Other potential limitations include the irregular spiking to high NO 3 – concentrations (atypical of most systems in reality), which could also affect microbial assemblage dynamics, though this could represent storm-driven high nutrient loading . Furthermore, high concentrations of DOC and associated metrics in treatments without sediment are not at all representative of instream wood in the surface water column of streams because, in these circumstances, DOC would be quickly transported .…”
Section: Discussionmentioning
confidence: 99%
“…72 Other potential limitations include the irregular spiking to high NO 3 − concentrations (atypical of most systems in reality), which could also affect microbial assemblage dynamics, though this could represent stormdriven high nutrient loading. 66 Furthermore, high concentrations of DOC and associated metrics in treatments without sediment are not at all representative of instream wood in the surface water column of streams because, in these circumstances, DOC would be quickly transported. 19 While these artifacts of the experimental design may prevent reliable inference and scaling of metrics to absolute values, the broad patterns observed here are likely to be somewhat representative of in situ observations.…”
Section: Consequences For Estimates Of Global Carbon and Nitrogen Cyclesmentioning
confidence: 99%
“…Recent work has highlighted the potential of benthic periphyton to accumulate excess P in oligotrophic streams in response to short duration pulses of elevated P concentration . Accumulation of excess P under conditions of high availability (i.e., luxury uptake) has also been observed in marine and freshwater phytoplankton in addition to benthic algae. Luxury uptake is achieved through intracellular conversion and storage of inorganic P molecules as polyphosphate polymers . Polyphosphate accumulation may therefore serve as an underappreciated mechanism of transient P retention in streams that receive short duration high concentrations inputs of P from overland flows or episodic point sources.…”
Section: Introductionmentioning
confidence: 99%